Systematic review for surgical treatment of adult and adolescent laryngotracheal stenosis. (21st October 2016) - Lewis, Sean; Earley, Marisa; Rosenfeld, Richard; Silverman, Joshua
Abstract : Objectives/Hypothesis: To determine if open surgical treatment options for adult and adolescent laryngotracheal stenosis are more successful than endoscopic procedures. Study Design: Systematic review. Methods: Embase and MEDLINE were searched for publications on adult and adolescent patients (>13 years old) with laryngotracheal stenosis. Cause of stenosis (intubation, idiopathic, or trauma) and treatments (open laryngotracheal resection with anastomosis, open laryngotracheal reconstruction with expansion grafting, or endoscopic procedures) were included. Primary outcomes are decreased additional surgery performed and success of decannulation, if previously tracheostomy. Results: There were 297 abstracts reviewed, 104 articles selected for full‐text review, and 39 articles, with 834 pooled patients, included in the analysis. Patients who had an open procedure (resection with anastomosis or reconstruction with expansion grafting) had significantly different outcomes rates; 32% versus 38% ( P <.001) received additional surgery and 89%and 83% ( P <.001) were decannulated, respectively. For patients who had endoscopic repair, 44% received additional surgery, and 63% were decannulated. Patients with idiopathic stenosis were more likely to receive additional surgery than those with traumatic (54% vs. 25%) and intubation/tracheostomy etiologies (54% vs. 35%). Etiology of stenosis did affect decannulation rates, patients with intubation/tracheostomy etiology had decannulation rates of 88%, compared to traumatic etiologies (78%, P <.001) and idiopathic stenosis (63%, P <.001). Risk of bias did not impact study results and was assessed using a validated instrument, Methodological Index for Non‐randomized Studies criteria. Conclusions: Patients with adult laryngotracheal stenosis who undergo laryngotracheal resection with anastomosis receive less surgery compared to those who undergo endoscopic treatment or laryngotracheal reconstruction with augmentation/grafting. Patients with idiopathic stenosis are less likely to receive further surgery compared to those from trauma or intubation/tracheostomy, but have the lowest rate of decannulation. Level of Evidence: NA Laryngoscope, 127:191–198, 2017